Bun-yat al-Manhâj Syibhu al-Muwâziyah li Qismi Ta’lîmi al-Lughati al-Arabiyyati bi Jâmi’ati Maulânâ Mâlik Ibrâhim al-Islâmiyati al-Hukûmiyati Mâlang: The Semi-Parallel Curriculum Structure for the Arabic Language Teaching Department at The State Islamic University of Maulana Malik Ibrahim Malang - Hadi, Nurul; Asrori, Imam; Hamid, M. Abdul (OKARA: Jurnal Bahasa dan Sastra, 2023)
The frequent changes in government policies regarding higher education curricula pose a problem for many universities. One recent policy that has caused issues is the "MBKM" curriculum, which also influences State Islamic Religious Colleges. This study aims to reveal how the Arabic Language Teaching Department of UIN Maulana Malik Ibrahim Malang developed a semi-parallel structure by combining parallel and serial structures. A case study approach was employed, with the Arabic language teaching department of UIN Maulana Malik Ibrahim Malang as the main research subject. Data was collected through interviews and documentation. The data analysis consisted of three stages: data reduction, data presentation, and conclusion drawing. The findings revealed that the semi-parallel curriculum structure implemented by the Arabic language teaching department fulfills two curriculum standards. Firstly, it meets the demand for curriculum standardization based on the Indonesian National Qualifications Framework (KKNI) outlined in Higher Education Regulation No. 44, 2015. Secondly, the semi-parallel curriculum structure corresponds to the curriculum standards set forth by the Indonesian Arabic Teachers Association (IMLA) in 2019. So, the development of a semi-parallel curriculum structure for the Arabic Language Teaching department has proven to be following national standards, even though policies often change.